PRESERVICE CLASSROOM TEACHERS’ BIOETHICAL PERCEPTIONS - ÖZKAN, Gülbin; UMDU TOPSAKAL, Ünsal (The Eurasia Proceedings of Educational and Social Sciences, 2016)
Recent developments in biology and biotechnology have raised ethical issues. In order to live in more ethical world, it is most important to improve preservice teachers' capacity to make ethical decisions. The purpose of this research was to determine preservice classroom teachers’ perceptions about bioethical issues. The research was conducted with 40 preservice class teachers (35 females, 5 males) from Yildiz Technical University, Faculty of Education, Department of Classroom Education in 2015-2016 academic year. In this study qualitative research method was used. For this purpose four bioethics scenarios was developed by the researchers and applied. The participants wrote their decisions about each scenario that included bioethical issues. The data was treated by qualitative data analysis - open coding. As a consequence of this research, it has been revealed that classroom teachers have decided mostly by their beliefs such as religious rather than bioethical perspective. At the end of the research, some suggestions were made concerning to have bioethics subjects in lessons, and to arrange preservice education for classroom teachers.